2012
DOI: 10.1155/2012/370385
|View full text |Cite
|
Sign up to set email alerts
|

Age of 40 Years or Younger Is an Independent Risk Factor for Locoregional Failure in Early Breast Cancer: A Single-Institutional Analysis in Saudi Arabia

Abstract: Background. This study was undertaken to evaluate the impact of prognostic factors on the locoregional failure-free survival of early breast cancer patients. Methods. In this single-institutional study, 213 breast cancer patients were retrospectively analysed. Fifty-five of 213 patients were ≤40 years of age at diagnosis. The impact of patient- or treatment-related factors on the locoregional failure-free survival was assessed using the Kaplan-Meier method. The simultaneous impact of factors on the locoregiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
26
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 76 publications
6
26
0
4
Order By: Relevance
“…They compared the features and management outcomes between younger and older age clusters, and the study showed being more youthful (age<or=40) to be an independent hazard element for BC relapse. Another research reviewed the epidemiology of BC cases in eastern province and they found that BC cases were detected at earlier age (<50 years: 57.5%) [16]. Other studies in different region in the kingdom and at different period reported the same range of age.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…They compared the features and management outcomes between younger and older age clusters, and the study showed being more youthful (age<or=40) to be an independent hazard element for BC relapse. Another research reviewed the epidemiology of BC cases in eastern province and they found that BC cases were detected at earlier age (<50 years: 57.5%) [16]. Other studies in different region in the kingdom and at different period reported the same range of age.…”
Section: Discussionmentioning
confidence: 95%
“…A selective literature review was done with the intention of providing information to enrich knowledge for the organization of screening, treatment, and preventative approaches for BC in KSA [21]. Other studies [16,[22][23][24][25][26] considered the risk factors of BC. Early identification of breast cancer is crucial and needs special attention.…”
Section: Significance Of the Studymentioning
confidence: 99%
See 2 more Smart Citations
“…Observa-se, então, que cerca de um terço à metade da população feminina afetada pela doença tem menos de 50 anos, e aproximadamente 10% tem menos de 40 anos 14,15 . O acometimento de mulheres mais jovens pelo câncer de mama parece ser, isoladamente, um fator de mau prognóstico (elevando a chance de recidiva loco regional 16 ), trazendo para essas mulheres uma nova necessidade de planejamento de vida, como a preocupação com a preservação da fertilidade (que pode ser afetada pela doença e pelos tratamentos) 14,15 .…”
Section: Discussionunclassified